2012
DOI: 10.1159/000338730
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelium Tears in Age-Related Macular Degeneration Treated with Antiangiogenic Drugs: A Controlled Study with Long Follow-Up

Abstract: Purpose: To study whether anti-vascular endothelial growth factor (VEGF) therapy improves visual acuity (VA) in patients with exudative age-related macular degeneration (AMD) complicated with retinal pigment epithelium (RPE) tears. Methods: Retrospective case-control series. Group I (control group) included 9 patients with RPE tears that received no treatment, and group II (intervention group) incorporated 12 patients treated with anti-VEGF. Results: A statistically significant difference was found in VA betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 76 publications
1
7
0
1
Order By: Relevance
“…Final visual acuity was worse for larger RPE tears (grades 3 and 4) when compared with smaller tears (grades 1 and 2), which is in accordance with findings by Sarraf et al [24]. Similar functional results were reported by Coco et al [47]. Improvements in visual acuity have also been reported in patients with spontaneous RPE tears who were subsequently treated with anti-VEGF therapy [48].…”
Section: Therapy After Tear Formationsupporting
confidence: 88%
“…Final visual acuity was worse for larger RPE tears (grades 3 and 4) when compared with smaller tears (grades 1 and 2), which is in accordance with findings by Sarraf et al [24]. Similar functional results were reported by Coco et al [47]. Improvements in visual acuity have also been reported in patients with spontaneous RPE tears who were subsequently treated with anti-VEGF therapy [48].…”
Section: Therapy After Tear Formationsupporting
confidence: 88%
“…They are commonly reported as adverse events in studies of patients undergoing intravitreal bevacizumab or ranibizumab injection [14 && ,29,31,32,37,40,42,47, 49,51,59,68,70]. In addition, neovascular AMD complicated by tears of RPE does improve with anti-VEGF therapy [99]. In addition, neovascular AMD complicated by tears of RPE does improve with anti-VEGF therapy [99].…”
Section: Tears Of the Retinal Pigment Epitheliummentioning
confidence: 99%
“…In the literature, some publications reported a worsening of VA due to the occurrence of an RPE tear after the anti-VEGF injection. Other studies reported no change (20) . However, long-term follow-up of these patients is required and when deciding on the course of treat ment to use, possible complications should be considered.…”
Section: Discussionmentioning
confidence: 92%